2019
DOI: 10.1016/s1569-9056(19)30439-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory functions of PD-L1 and PD-L2 in the regulation of anti-tumor immunity in murine tumor microenvironment

Abstract: PD-L1 expressed on tumor cells and bone marrow-derived hematopoietic cells, as well as PD-L2 inducibly expressed on tumor-associated macrophages, play an important role in the suppression of anti-tumor immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The tendency of EGFR ‐mutated NSCLC with high PD‐L1 expression to coexpress PD‐L2 through extrinsic or intrinsic mechanisms remains elusive in the context of basic research. However, the observation of highest PD‐L2 coexpression in type 1 tumors compared to other TME types could be reasonable evidence that type 1 tumors might benefit better from anti‐PD‐1 therapies than from anti‐PD‐L1 therapies in the clinical context . Further clinical evaluation is warranted to support this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…The tendency of EGFR ‐mutated NSCLC with high PD‐L1 expression to coexpress PD‐L2 through extrinsic or intrinsic mechanisms remains elusive in the context of basic research. However, the observation of highest PD‐L2 coexpression in type 1 tumors compared to other TME types could be reasonable evidence that type 1 tumors might benefit better from anti‐PD‐1 therapies than from anti‐PD‐L1 therapies in the clinical context . Further clinical evaluation is warranted to support this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…We expected better clinical efficacy with anti‐PD‐1 Ab (nivolumab) plus carboplatin/paclitaxel/bevacizumab than anti‐PD‐L1 based on the strength of preclinical findings and previously described clinical studies. Preclinical studies indicated that combined PD‐L1/PD‐L2 blockade on dendritic cells augmented T cell proliferation and cytokine production more effectively than PD‐L1 blockade alone, 19 and that anti‐PD‐1 Abs might be more effective, by blocking the interaction between PD‐1 and both PD‐L1/PD‐L2, than anti‐PD‐L1 Abs, which only block the PD‐1/PD‐L1 interaction 20 …”
Section: Discussionmentioning
confidence: 99%
“…The in vivo study focused on the mechanism of how the ligand for PD‐1 regulates antitumor immunity revealed that the TAM‐derived PD‐L1 contributes predominantly to suppress antitumor immunity than the host‐derived one. Further investigation indicated the importance of TAM‐expressed PD‐L2, another ligand for PD‐1, in the suppression of antitumor immunity . In fact, the immunosuppressive activity of TAMs is largely depended on the cytokines liberation that acts on T cells and the subsets.…”
Section: Immunity In Cancermentioning
confidence: 99%